Studi Pendahuluan Kayu Mahoni Merah (Eucalyptus pellita F. Muell) Dari Kalimantan Tengah: Preliminary Study Of Red Mahogany Wood (Eucalyptus pellita F. Muell) From Central Kalimantan - Grace Siska; Lies Indrayanti; Eva Oktoberyani Christy; Sari Marlina (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Eucalyptus pellita is one of the potential plant choices as raw material for the pulp and paper industry in Indonesia. The Eucalyptus pellita F. Muell species has several species, one of which is red mahogany. Red mahogany is a type of plant in industrial plantation forests that is very good for industrial plantation forest business permit holders. This study aims to determine the physical and mechanical properties of red mahogany wood in the axial direction of the stem. The results of the study show that the analysis of variance in testing physical properties, namely moisture content and mechanical properties of red mahogany wood, , modulus of elasticity (MoE), modulus of rupture (MoR), hardness does not have a significant effect on the stem section but density is significantly different at the base of the wood